Analysis of Financial Ratios on the Performance of PDAM Tirta Waesai, Barru Regency - Firdaus, Ahmad; Siswanto, Adi; Mariana, Lina (Jurnal Ekonomi Balance, 2022)
The objectives of this study are: To analyze Financial Ratios to assess the performance of PDAM Tirta Waesai, Barru Regency. This study discusses Liquidity Ratio Analysis and Profitability. The data used in this study are primary data and secondary data. The type of research used is descriptive quantitative research that aims to find factual information. The object used in this study is the financial report in the form of a Balance Sheet and Loss Report of PDAM Tirta Waesai Kab Barru for the period 2016 to 2020. The data analysis method used is Time Series financial performance analysis. The results of the study seen from the liquidity ratio based on the current ratio, it can be said that PDAM Tirta Waesai has a good ability to pay off its debts. If viewed from the profitability ratio based on ROI, PDAM Tirta Waesai is still in a net loss condition.